Use of Abattoir Wastewater Compost as Organic Fertilizer for Rice Production on a Ultisol in Delta State, Nigeria - Ojobor, Smart Augustine; Egbuchua, Collins N (Asian Journal of Agriculture and Rural Development, 2020)
The research was conducted to monitor the influent of abattoir wastewater compost on rice growth and yield in Benin-Owah River Basin in Illah, Delta State, Nigeria. The compost was applied at 0, 2.5, 5.0, 10 t/ha, and NPK15:15:15 at 250 kg/ha laid in randomized complete block design with four replicates. Rice seeds were sown for two years, and residual effects were evaluated in the third year. Rice plant height, stem circumference, and the number of tillers was measured at two weeks intervals while rice yields have taken at harvest. Soil samples were taken yearly to monitor nutrient changes. Data obtained were analyzed with analysis of variance and mean separated with Duncan Multiple Range Test at α0.05. In the first year, NPK15:15:15 significantly gave the highest dry matter (6.28±1.45 t/ha) and grain yield (2.4±0.53 t/ha). While in the second year, 10 t/ha treatment produced the dry matter (7.69±1.60 t/ha) and grain yield (2.6±0.53 t/ha). In a residual study, the highest grain yield (2.8±0.72 t/ha) was produced in the plot treated with 10 t/ha, and it also gave the highest pH, organic carbon, total nitrogen, and available P content. The compost at the rate of 10 t/ha can increase soil fertility and rice yield.